Effect of Fundus Fluorescein Angiography on Semiautomated Aqueous Flare Measurements. (17th February 2022) - Halim, Muhammad Sohail; Onghanseng, Neil; Park, Jung Hyun; yilmaz, Mervenur; Segawa, Asadu; Ertop, Mestan; Hassan, Muhammad; Tran, Anh Nt; Aktas, Zeynep; Ozdek, Sengul; Gurelik, Gokhan; Do, Diana V.; et al.
ABSTRACT: Purpose: To evaluate the effects of fluorescein fundus angiography (FFA) on semiautomated aqueous flare measurements Methods: Laser flare photometer (LFP) measurements was performed at baseline, 30 min, and 4 h after the intravenous administration of sodium fluorescein dye. FFA was performed immediately after the baseline LFP measurement. LFP values at 30 min and 4 h after FFA were compared to baseline values. Mean change in LFP measurements at 30 min and 4 hafter baseline was compared between FFA arm and controls. Results: The mean flare measurement in the FFA and control arm dropped 6% ( p value = 0.002) and 9% ( p value = 0.04), respectively. Mean change in LFP measurement at 30 min and 4 h after baseline was not significant between FFA arm and controls. Conclusions: Administration of fluorescein dye does not increase LFP values. The decrease in the LFP measurement following FFA may be attributed to dilation drops.